PENERAPAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) DALAM MENGANALISIS LOGAM MERKURI (Hg) PADA KRIM PEMUTIH WAJAH - Nurbaya, Siti; Safwan, Ahmad Gazali; Silitonga, Maringan (Jurnal Farmanesia, 2019)
Whitening cream is a mixture of chemicals and or other ingredients with properties that can fade dark spots on the skin. Whitening cream must be safe and must not contain harmful ingredients such as heavy metal mercury because its toxicity to the organs of the kidneys, nerves, and brain is very strong, so its use is prohibited in cosmetic preparations. The purpose of this study was to determine the levels of metallic mercury (Hg) contained in the preparation of facial whitening creams circulating in Sei Sikambing Market, Medan. The sample used in this study was a facial whitening cream that was not registered with BPOM. The method used to determine mercury levels is qualitatively using color reagents and quantitatively using AAS (Atomic Absorption Spectrophotometry). The results obtained were from 2 samples of facial whitening cream that were used positively for heavy metal mercury (Hg) characterized by the formation of a red-orange precipitate with KI reagent, yellow precipitate by NaOH reagent, white precipitate by HCl reagent. The results of the analysis showed that the highest Hg metal content in the sample with code E was 5.0241 ± 0.4064 g/g. The conclusion of this study is that two samples were positive for mercury, where the use of mercury has been prohibited by BPOM.